2017
DOI: 10.1016/j.neuron.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal Nets in the Adult Sensory Cortex Are Necessary for Fear Learning

Abstract: Summary Lattice-like structures known as perineuronal nets (PNNs) are key components of the extracellular matrix (ECM). Once fully crystallized by adulthood, they are largely stable throughout life. Contrary to previous reports that PNNs inhibit processes involving plasticity, here we report that the dynamic regulation of PNN expression in the adult auditory cortex is vital for fear learning and consolidation in response to pure tones. Specifically, after first confirming the necessity of auditory cortical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 71 publications
7
108
0
Order By: Relevance
“…We present, to our knowledge for the first time, evidence that WFA+ PNN vary according to diurnal rhythms in the human brain and to diurnal and circadian rhythms in the rodent brain. Our data adds to a growing number of studies demonstrating that PNNs are dynamic structures, responding to the environment and potentially contributing to memory consolidation during sleep (Balmer et al, 2009;Brown et al, 2009;Banerjee et al, 2017;Dingess et al, 2018;Slaker et al, 2018), We show that numbers of WFA+ PNN follow diurnal rhythms in several brain regions in mouse and in human. Importantly, we show that WFA+PNN rhythmicity occurs in mice kept in constant darkness, supporting the claim that these changes reflect circadian rhythms rather than a response to light-dark cycles (Fig.6).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…We present, to our knowledge for the first time, evidence that WFA+ PNN vary according to diurnal rhythms in the human brain and to diurnal and circadian rhythms in the rodent brain. Our data adds to a growing number of studies demonstrating that PNNs are dynamic structures, responding to the environment and potentially contributing to memory consolidation during sleep (Balmer et al, 2009;Brown et al, 2009;Banerjee et al, 2017;Dingess et al, 2018;Slaker et al, 2018), We show that numbers of WFA+ PNN follow diurnal rhythms in several brain regions in mouse and in human. Importantly, we show that WFA+PNN rhythmicity occurs in mice kept in constant darkness, supporting the claim that these changes reflect circadian rhythms rather than a response to light-dark cycles (Fig.6).…”
Section: Discussionsupporting
confidence: 60%
“…PNNs are well represented in neural circuits involved in emotion processing and critically involved in the regulation of fear and reward memories (Gogolla et al, 2009;Slaker et al, 2015;Banerjee et al, 2017;Lasek et al, 2018). Consistent with these observations, PNNs have been implicated in several brain disorders involving these regions, including schizophrenia, bipolar disorder, Alzheimer's disease and addiction (Baig et al, 2005;Morawski et al, 2010;Pantazopoulos et al, 2010a;Mauney et al, 2013;Xue et al, 2014;Pantazopoulos et al, 2015;Slaker et al, 2015;Steullet et al, 2017;Blacktop and Sorg, 2018).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Sorg et al, 2016;Ueno et al, 2019). Experiments involving the enzymatic removal of PNN by chondroitinase ABC (ChABC) or hyaluronidase injections in amygdala, hippocampus, piriform and auditory cortices have shown that synaptic plasticity can be reactivated (Banerjee et al, 2017;Gogolla et al, 2009;Kochlamazashvili et al, 2010;Krishnan, Lau et al, 2017;Pizzorusso et al, 2002;Thompson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%